THE EFFECT OF INCREASING LEVEL OF PALM KERNEL MEAL AND COPRA MEAL ON DIET TO THE MICROBIAL PROTEIN PRODUCTION IN THE RUMEN OF STEERS FED LOW QUALITY FORAGE - MARSETYO, MARSETYO (Majalah Ilmiah Peternakan, 2012)
SUMMARY The effect of increasing the level of palm kernel meal (PKM) and copra meal (CM) supplementation on the diet to the microbial crude protein (MCP) production, efficiency of microbial protein production (eMCP) in the rumen and rumen fluid conditions of Brahman crossbred steers given low quality forage based diet has been studied. Ten steers (243?b6.5 kg) were allocated to two supplement types diets (PKM and CM). The experimental design included two incomplete 5x5 Latin Squares, each with three runs, for three months. Each run consisted of a 14 d adaptation and 7 d collection period. Steers received Green panic grass hay ad libitum with one of five levels of PKM or CM (0.00, 0.25, 0.50, 0.75 and 1.00% of body weight (W) per day (d)). MCP production responded linearly (P<0.05) with increasing PKM or CM intakes. eMCP and rumen NH3-N concentration (taken at 3 and 24 h after feeding) responded quadratically (P<0.05) with increasing PKM or CM intakes. It was concluded that supplementation of both PKM and CM up to level of 1.0% W/day resulted in significant increase in MCP production and eMCP in the rumen. These increases were partly due to the increasing of the concentration of rumen NH3-N in the rumen as a result of increasing supplement intakes.